On Some Properties of Parametric Quadratic Programs Pertaining to Continuous-time Quadratic Fractional Programming - Ching-Feng Wen; Yung-Yih Lur; Wen-Hsien Ho; Jyh-Horng Chou (2012 Fifth International Joint Conference on Computational Sciences and Optimization, 2012)
This article is concerned with quadratic fractional optimal control problems with linear state constraints. Such problems are called the {\em continuous-time quadratic fractional programming problems} (CQFP). Some basic properties of parametric continuous-time quadratic programming problems pertaining to (CQFP) are derived. By these properties, (CQFP) can be reduced to continuous-time quadratic programming problems. Besides, a discretization approach for solving continuous-time quadratic programming problems is also developed. The developed approach will provide an important foundation for constructing a parametric computational procedure for (CQFP).